Evaluasi Kesiapan Dan Penerimaan Pengguna Sistem Informasi Management Tugas Akhir (SIMTEKNIK) Menggunakan Metode TRAM (Technology Readiness Acceptance Model) - Lailatul Hasanah; Evi Dwi Wahyuni; Wildan Suharso (Jurnal Repositor, 2020)
SIMTEKNIK is an information system used by students of the Faculty of Engineering of the poor university of Muhammadiyah University which is usually used for activities related to the demands of the final project or thesis. SIMTEKNIK itself is a new information system that is used so that where there are found a number of system-related problems such as interface the existingthat is not yetenough friendly, and is less comfortable with the display of color writing to the system design, difficulty finding multiple menus when first used up to the waiting time when uploading files including long. Based on these problems, it is necessary to do an analysis to find out how user acceptance and readiness of SIMTEKNIK. Analysis of user readiness and acceptance needs to be done because the first step that must be done in implementing technology is knowing the user's readiness in accepting the technology. As for the model used in this study is the TRAM method (Technology Readiness Acceptance Model) The TRAM method is a combination of the Technology Readiness Index and the Technology Acceptance Model that was first proposed by Lin et al in 2005. The results found that from 9 hypotheses there were 5 hypotheses that were accepted and 4 others were rejected. accepted hypothesis namely, OPT-> PEU, INN-> PEU, DIS-> PU, DIS-> PEU and PEU-> PU .